PARTISIPASI PEREMPUAN DALAM PUSARAN PEMBANGUNAN DAERAH (Telaah Kritis Atas Kendala Dan Solusi) - Shinta Dewi Rismawati (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2012)
Women's participation in any development process is very important and strategic in the context of policy decisions that is favored of women. The assumption is, that women as members of society is basically have the same chances and opportunities to participate in every stage of development, since women are also the subject of development. However, there are many obstacles and barriers to encourage women to participate actively, for instances: internal or external constraints. Internal herein is relating to personal / individual of the women themselves (aspect of psychological-personality). Whereas external here is associated with things that are outside of the women themselves (structural and cultural). Thus, the solution is also varies from internal and external as well, such as increasing the capacity building for women and the socialization and education concerning the true concept of gender to the public.